The impact of brand gender on consumer-brand engagement and consumer-based brand equity on Facebook - Machado, Joana César (2019)
In this research, we investigate how two distinct and universal dimensions of brand personality - brand masculinity and brand femininity - which constitute the two dimensions of brand gender (Grohmann 2009) influence consumer-brand engagement on Facebook. Another critical aim is to investigate the relationship between brand masculinity and brand femininity perceptions and consumer-based brand equity, on Facebook.